Case Report: Intragastric balloon placement for weight loss in LVAD patients—a bridge to heart transplantation - Desai, Aarti; Sharma, Shriya; Siaw, ADJ; Ruiz, Jose; Gómez, Victoria; Goswami, Rohan (Frontiers in Cardiovascular Medicine, 2025)
Obesity significantly increases the risk of advanced heart failure, complicating heart transplantation candidacy. Despite aggressive medical therapies, achieving weight loss in these patients remains challenging, especially in patients after durable ventricular assist device (LVAD). More intense weight loss interventions such as bariatric and metabolic surgery and endoscopic bariatric therapies (EBTs) can lead to meaningful weight reduction, enabling previously ineligible individuals to become transplant candidates. A 51-year-old gentleman with end-stage heart and kidney failure status-post HeartMate 3 LVAD (Abbott, Chicago, IL) and Class II obesity (BMI 36.5 kg/m2), was deemed ineligible for heart transplant due to high BMI (≥35 kg/m2). Despite lifestyle modification, he was unable to lose weight, and BMI increased to 40.8 kg/m2 over the next 10 months. A multi-disciplinary discussion was held to discuss possible weight loss options, and after careful consideration, bariatric surgery was not deemed safe. The decision was made to proceed with EBTs, and an intragastric balloon (IGB) was successfully placed as a bridge to heart transplant. The IGB was removed at the six-month period per standard of care, and the patient had lost 16.5 Kg, achieving a 12.4% Total Body Weight Loss with a BMI of 35.3 kg/m2. The patient underwent successful heart and kidney transplant and is now two months post-transplant. His BMI 2-months post-transplant is 37 kg/m2. This case highlights the feasibility and efficacy of EBT therapy with IGB placement as an alternative to bariatric surgery for patients with LVAD placement and significant comorbidities who need to lose clinically significant weight to be deemed eligible for heart transplant.